Girls for sale : a play from colonial India = Kanyasulkam - Apparao, Gurujada Venkata, 1861-1915 (Book collections on Project MUSE., 2007)
First staged in 1892, the South Indian play Girls for Sale (Kanyasulkam) is considered the greatest modern work of Telugu literature and the first major drama written in an Indian language that critiqued British colonialism's effects on Indian society. Filled with humor, biting social commentary, parody, and masquerade, the plot revolves around a clever courtesan, a young widow, and a very old man who wants to buy as his wife a very young girl. Velcheru Narayana Rao has prepared the first idiomatic Englis.